Asymptotic Formula for Oscillatory Solutions of Some Singular Nonlinear Differential Equation - Irena Rachůnková; Lukáš Rachůnek (Abstract and Applied Analysis)
Singular differential equation (p(t)u′)′=p(t)f(u) is investigated. Here f is Lipschitz continuous on ℝ and has at least two zeros 0 and L>0 . The function p is continuous on [0,∞) and has a positive continuous derivative on (0,∞) and p(0)=0. An asymptotic formula for oscillatory solutions is derived.